2014
DOI: 10.7314/apjcp.2014.15.13.5469
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Acceptance, and Willingness to Pay for Human Papilloma Virus (HPV) Vaccination among Female Parents in Thailand

Abstract: Background: This study aimed to examine the level of knowledge, attitude, acceptance, and willingness to pay (WTP) for HPV vaccination among female parents of girls aged 12-15 years in Thailand. Materials and Methods: A cross-sectional survey was conducted in eight schools across Bangkok. Results: Of 1,200 questionnaires sent out, a total of 861 questionnaires were received. Knowledge regarding the HPV vaccine among parents was quite low. Only half of the parents knew about the link between HPV and cervical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
44
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 32 publications
6
44
0
4
Order By: Relevance
“…At the time of the present study, HPV vaccination was not included in the Thai national immunization program. The result confirms previous studies conducted in Thailand that reported high acceptance of the HPV vaccine if it was offered for free . In 2018, the HPV vaccine will become available throughout Thailand free of charge for approximately 400 000 Thai girls aged 9 years studying in grade 5.…”
Section: Discussionsupporting
confidence: 86%
“…At the time of the present study, HPV vaccination was not included in the Thai national immunization program. The result confirms previous studies conducted in Thailand that reported high acceptance of the HPV vaccine if it was offered for free . In 2018, the HPV vaccine will become available throughout Thailand free of charge for approximately 400 000 Thai girls aged 9 years studying in grade 5.…”
Section: Discussionsupporting
confidence: 86%
“…These results were higher than in other studies conducted in literature. (Karadag et al, 2014;Kruiroongroj et al, 2014). Correct answers for HPV-related statements were low in between who answered 'Some viruses may cancer' correct.…”
Section: Discussionmentioning
confidence: 97%
“…While studies in Turkey which's topic is about early age of first intercourse causing cervical cancer was between 2.9%-86.5% (Ertem, 2009;Uysal and Birsel, 2009;Bekar et al, 2013;Coskun et al, 2013;Sogukpınar et al, 2013;Karadag et al, 2014;Yilmazel and Duman, 2014). In studies conducted outside of Turkey the results was found between 18.3%-68.8% (Khoo et al, 2011;Hoque et al, 2013;Thippeveeranna et al, 2013;Al-Darwish et al, 2014;Kruiroongroj et al, 2014). Research results were various in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…In California, Robitz et al (2011) stated that 45.7% of the families had never heard of vaccination previously. In Kruiroongroj et al (2014)'s study, majority of the respondents (70%) were aware of the HPV vaccine.…”
Section: Discussionmentioning
confidence: 97%
“…In Ghojazadeh et al (2012)'s study, parents' 42% claimed that they had obtained such information by studying medical resıources and 36% from Internet and friends. In Kruiroongroj et al (2014)'s study, Tv/radio, newspapers/magazines (88%) were major information, followed by hospital /health care providers (66%).…”
Section: Discussionmentioning
confidence: 99%